2015
DOI: 10.1108/jwl-02-2014-0011
|View full text |Cite
|
Sign up to set email alerts
|

Self-regulated learning behaviour in the finance industry

Abstract: Purpose As work practices in knowledge intensive domains become more complex, individual workers must take greater responsibility for their ongoing learning and development. This study seeks to explore the role of self-regulatory behaviours in predicting workplace learning. Design/methodology/approach The study was conducted with knowledge workers from the finance industry. 170 participants across a range of work roles completed a questionnaire consisting of three scales derived from validated instruments (mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 33 publications
2
35
1
Order By: Relevance
“…Interestingly, so far, the scarce empirical research has indicated self-directedness and SDL to be self-evident aspects (Moe et al 2008) of contemporary agile and low hierarcy companies (Holbeche 2015). However, despite the increasing importance of SDL in ICT work (Ha 2008;Milligan et al 2015;Germain and Grenier 2015), our findings indicate that learning should not become totally self-driven, as is the aim in some contemporary low-hierarchy, self-organising enterprises (cf. Lee and Edmondson 2017).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Interestingly, so far, the scarce empirical research has indicated self-directedness and SDL to be self-evident aspects (Moe et al 2008) of contemporary agile and low hierarcy companies (Holbeche 2015). However, despite the increasing importance of SDL in ICT work (Ha 2008;Milligan et al 2015;Germain and Grenier 2015), our findings indicate that learning should not become totally self-driven, as is the aim in some contemporary low-hierarchy, self-organising enterprises (cf. Lee and Edmondson 2017).…”
Section: Discussionmentioning
confidence: 65%
“…Although, there has been earlier research on learning practices at work, some researchers have argued that studies on the topic have been too theoretical and have lacked empirical evidence (Lee and Roth 2006). Some of the empirical studies have been conducted as ethnographic case studies (e.g., Valleala et al 2015) or primarily based on interviews and surveys (e.g., Milligan et al 2015;Vanthournout et al 2014). However, there is a need also for in-depth tools to understand learning and SDL as phenomena in the context of work and to determine the learning methods or resources employees use to achieve their learning goals (Pintrich 2004;Ha 2008;Loftus and Higgs 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The different sub-processes of self-regulated learning are of course highly inter-connected, with evidence from quantitative studies using self-report instruments to measure these sub-processes indicating that they are strongly correlated (Littlejohn et al, 2016b, Milligan et al, 2015) in different populations. Bringing together the four sub-process described here, some clear patterns of learning emerge that illustrate their inter-relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Goal setting, Strategic planning, Self-efficacy, Task interest and value, Task strategy, Elaboration, Critical thinking, Self-evaluation, and Self-satisfaction. Linear regression analysis probed the relationship between self-regulated learning and workplace learning activity (n = 170: Milligan et al 2015). There was a positive relationship between self-regulated learning and workplace learning activity, with higher SRL (as perceived by the learners and measured by the SRLWQ) predicting greater uptake of professional learning opportunities outside education and training.…”
Section: Foundations Of This Studymentioning
confidence: 99%